Participation of Forest Encroachers in Participatory Ecosystem Restoration Program in Dangku Wildlife Reserve, Musi Banyuasin - Indra Purnama Bahri; Sriati Sriati; Sarno Sarno (Sriwijaya Journal of Environment, 2021)
Conservation forest areas in Indonesia cannot be separated from threats and damage. The amount of forest area in Indonesia that continues to decrease is the reason for the importance of resolving the problems that exist in Indonesia's forest areas. One of the conservation areas that is facing serious threat is SM Dangku in Musi Banyuasin Regency. Land conversion and forest encroachment are become serious problems that have not been resolved properly. The participatory ecosystem restoration program at Dangku Wildlife Reserve is expected to be one of the right steps to restore the degraded conservation forest area. The positive impacts that came from the implementation of this program are the reduction in the number of new land clearing by the community, the increased willingness of the community to plant trees on farming land, and the decrease in the number of encroacher living in the area. In order to determine the factors that influence the success of the program, a research on the perception and participation of the forest encroacher in supporting the participatory ecosystem restoration program in Dangku Wildlife Reserve was carried out. The research was conducted using a survey method with a qualitative approach. The results showed that the participation of the forest encroacher in the participatory ecosystem restoration program was moderate, although the level of perception of the forest encroacher towards the program was quite good. One of the factors that influence this condition is that the benefits derived from the program are not in line with the expectations and needs of the encroaching communities.